Balance Scorecard Analysis Poverty Reduction Performance Through The Cash Social Assistance Program Study in Neglasari District, Tangerang City - Edi Mulyadi; Ahmad Yani; Tommy Andrian Suatrat (CV. Ridwan Publisher, 2023)
This study aims to identify and analyze the effectiveness of the Cash Social Assistance (BST) program during the Covid-19 Pandemic in Neglasari District, Tangerang City. The research uses a descriptive approach by describing the research object as reality through the translation of the numbers described with explanations in accordance with the calculated results on the indicators that affect the research object. The results of the study show that from a service perspective, from the respondent's point of view, 70.84 percent said they were satisfied with the accuracy of the target, this was because after all they were BST recipients. In the socialization process for disbursement schedules of funds and complaints when problems occur, officials feel dissatisfaction more often than BST recipients. From an internal performance perspective, based on BPS criteria, the variables that determine poverty are divided into 2, namely monetary variables based on the amount of expenditure, and non-monetary variables. From a development perspective, the majority of respondents, namely 98.33 percent, stated that they were happy with this BST, and 96.67 percent stated that the BST program was useful. As much as 80. 83 percent of respondents saw that this BST was able to reduce the burden of spending, but 82.50 percent stated that they had not experienced an increase in purchasing power after receiving the BST. From a financial perspective, the strength lies in how the government makes accountability reports and the principle of transparency to the public. With transparency and accountability in government financial management, it will gain the trust and support of the public.